ANALISIS KEBUTUHAN MEDIA POP-UP BOOK DALAM PEMBELAJARAN SENI BATIK DAN ANYAMAN UNTUK ANAK USIA DINI - Ramdhani, Tasya Nur; Loita, Aini; Alia, Dwi (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
Introducing local culture from an early age plays a crucial role in shaping children's identity. However, many early childhood education institutions (PAUD) do not have a structured cultural education program, particularly in introducing the arts of batik and weaving. This study aims to analyze the need for local culture-based learning media for early childhood as a foundation for developing a Pop-Up Book. A qualitative descriptive method was employed as the initial stage of the Educational Design Research (EDR) approach. Data were collected through observations, interviews, and documentation at three early childhood education centers in Tasikmalaya. The results indicate that teaching methods are still dominated by lectures and have not effectively utilized visual media. Teachers expressed a need for concrete, engaging, and user-friendly learning tools, while children showed high interest in interactive media. Pop-Up storybooks are considered highly potential as cultural learning media suited to the developmental characteristics of early childhood. These findings serve as a critical foundation for developing relevant, contextual, and innovative learning media.